Does state antitrust enforcement drive establishment exit? - Robert M. Feinberg; Thomas A. Husted; Florian Szücs (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Previous work has shown that state-level antitrust enforcement activity may have impacts on entry and relocation behavior by U.S. firms. Significant state-level antitrust activity may be an indicator of a perceived adverse business environment and it is found to deter establishment entry, particularly for larger firms in the retail and wholesale sectors. An obvious question is whether establishment exit is affected in a symmetric way, or whether sunk costs of market entry may lead to a smaller impact in terms of the exit decisions. We first combine US Census establishment exit panel data with data for 1998-2006 on US state-level antitrust activity and other measures of state-level business activities that may affect establishment exit. We also consider establishment exit across different broad industry types - manufacturing, retail and wholesale - and several firm size categories. Local business cycle factors seem to be the primary driver of exit, though there is some evidence of political and antitrust determinants as well. In another approach, we examine firmlevel exit decisions and the extent to which these respond to state antitrust enforcement, with some indication of antitrust enforcement effects here as well, especially in the wholesale and retail sectors.
Keywords: K21; L41; L60; L81; 330; antitrust enforcement; state level; firm exit